The influence of dietary fat and intestinal pH on calcium bioaccessibility: an in vitro study. Issue 3 (7th March 2018) - Bandali, E.; Wang, Y.; Lan, Y.; Rogers, M. A.; Shapses, S. A.
Abstract : In vivo studies measuring true fractional calcium (Ca) absorption have shown that dietary fat is a significant predictor of absorption and is influenced by luminal pH levels. Abstract : In vivo studies measuring true fractional calcium (Ca) absorption have shown that dietary fat is a significant predictor of absorption and is influenced by luminal pH levels. However, whether changes in Ca bioaccessibility (CaB) can explain the effects on absorption has not been examined. In the current study, we examined two high fat diets enriched in either monounsaturated fatty acids or saturated fatty acids (SFA), and a low-fat diet (LFD), each with 50 mg Ca, and measured CaB at different intestinal regions during normal acidic or higher (pH = 7) gastrointestinal conditions using an in vitro gastrointestinal model. During normal pH conditions in the jejunum, there was an interaction between diet and time for CaB ( P < 0.02), and CaB during the SFA diet was higher than LFD ( P = 0.05). CaB was reduced by 90 ± 3% during higher compared with normal pH under all dietary conditions ( P < 0.001). These findings indicate that fat intake, especially SFA enriched, is associated with a greater CaB in the jejunum, and may explain the higher Ca absorption in previous studies. In addition, the marked reduction in CaB under higher pH conditions could have implications in persons taking medications to reduce gastric acid.